Simple Synthetic Receptors for Aspirin - Nguyen, Thanh Vinh; Sherburn, M. (Wiley - V C H Verlag GmbH & Co. KGaA, 2014)
Shallow methylene-bridged cavitands appended with simple H-bond donor/acceptor groups are shown tobind aspirin. The structural features needed in a synthetic receptor for aspirin binding are defined.